Selectively adsorptive extraction of phenylarsonic acids in chicken tissue by carboxymethyl α-cyclodextrin immobilized Fe3O4 magnetic nanoparticles followed ultra performance liquid chromatography coupled tandem mass spectrometry detection. - Jing Jia; Wei Zhang; Jing Wang; Peilong Wang; Ruohua Zhu (PLoS ONE, 2014)
Carboxymethyl α-cyclodextrin immobilized Fe3O4 magnetic nanoparticles (CM-α-CD-Fe3O4) were synthesized for the selectively adsorptive extraction of five phenylarsonic acids including p-amino phenylarsonic acid, p-nitro phenylarsonic acid, p-hydroxy phenylarsonic acid, p-acylamino phenylarsonic acid and p-hydroxy-3-nitro phenylarsonic acid in chicken tissue. Using ultra performance liquid chromatography coupled with tandem mass spectrometry (UPLC-MS/MS), a highly sensitive analytical method was proposed for the determination of five phenylarsonic acids. It was shown that CM-α-CD-Fe3O4 could extract the five phenylarsonic acids in complex chicken tissue samples with high extraction efficiency. Under the optimal conditions, a high enrichment factor, ranging from 349 to 606 fold, was obtained. The limits of detection (LODs) (at a signal-to-noise ratio of 3) were in the range of 0.05-0.11 µg/kg for the five phenylarsonic acids. The proposed method was applied for the determination of five target phenylarsonic acids in chicken muscle and liver samples. Recoveries for the spiked samples with 0.2 µg/kg, 2.0 µg/kg and 20 µg/kg of each phenylarsonic acids were in the range of 77.2%-110.2%, with a relative standard deviation (RSD) of less than 12.5%.